Misconceptions on chemical bonding among form four pupils / Quah Mei Ling - Quah , Mei Ling (2020)
The learning of chemical bonding in chemistry is an abstract concept for all students. The process of learning chemistry can be classified into three levels which are macroscopic, sub-microscopic, and symbolic levels. Students have problems correlating all three levels in learning chemical bonding. During the transition of these three levels, students face difficulties in relating the macroscopic and sub-microscopic levels which lead to misconceptions. Therefore, the purpose of conducting this study was to explore the misconceptions of chemical bonding which includes ionic bonding and covalent bonding among Form Four students. This study aimed to answer two research questions; 1) what are the misconceptions (if any) of chemical bonding among Form Four students and 2) how is the misconceptions on chemical bonding among Form Four students. A mixed-method design was applied to this research. The type of mixed method design starting with quantitative method and followed by qualitative method. In the first phase, which was the quantitative method, the participants were selected by convenient sampling where a total of 36 participants were selected. All the participants selected were given a two-tier diagnostic test to answer within 20 minutes. The data collected was analyzed descriptively to answer research question one. The second phase was the qualitative method, where 7 students were selected based on their diagnostic test scores to be interviewed in-depth on their misconceptions. These students were purposively selected for having the lowest scores. The findings showed that students have conceptual misunderstanding and factual misconception on chemical bonding and these misconceptions are students unable to differentiate ionic and covalent bonding, students failed to identify the type of particles in ionic and covalent bonding and students unable to construct the structure for ionic bonding. Lastly, students failed to apply proton number and valency of electron of an element which needed for students to interpret the chemical bonding.